Kurumsal kuramın kurumsallaşması: Türkiye kaynaklı kurumsal kuram çalışmalarına ilişkin genel bir değerlendirme - (:unkn) unknown (My University, 2014)
Bu çalışma, Kurumsal Kuram’ın Türkiye’deki evrimini, 2000 – 2010 yılları arasında Ulusal Yönetim ve Organizasyon Kongresi’nde (UYOK) sunulan bildiriler ve bu bildirilerde adı geçen araştırmacıların kongre harici yayınları üzerinden incelemektedir. Bu bağlamda, çalışma, bahsi geçen yıllar arasında, Türkiye'de kurumsal kuramın yönetim ve örgüt bilimciler arasında bir çalışma alanı olarak nasıl yayıldığına, bu yayılımda kurumsal girişimcilerin izlerine, Türkiye’de kurumsal kuramın araştırmaya konu edilen alt çalışma alanlarının merkez ülke olan ABD’deki çalışma alanlarıyla ne derece paralel olduğuna, Türkiye’de kurumsal kuram çalışmalarının metodolojik özelliklerine ve UYOK’da sunulan kurumsal kuram konulu bildirilerin yayına dönüşme süreçlerine ilişkin bulgular sunmaktadır.

This study investigates the evolution of institutional theory in Turkey through the papers that appeared at the National Management and Organization Conferences between 2000-2010, besides other works of those papers' authors. In this context, this study reveals how institutional theory studies became an important subfield among management and organization researchers in Turkey. Additionally, this study explains the signs of the institutional entrepreneurs in the diffusion of institutional theory studies in Turkey; compares the Turkey-based institutional theory studies with the studies from USA; analyzes the methodological features of Turkey-based institutional theory studies; and finally, reveals the relationship between presenting an institutional theory related paper at the National Management and Organization Conference and its transformation to become a journal article.
Institutionalization of institutional theory: A general analysis of Turkey- based institutional theory studies
Keywords: İletişim; Sosyoloji